Formulation of Feeds Intended For Livestock of Cyprinus Carpio in the Vakinankaratra Region, Madagascar - Rabarison Rindra; Ravelomanantsoa Ramanambe Nicole; Rabeharitsara Andry Tahina; Rakotomamonjy Pierre; Razafimahefa Mirana Verohanitra; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2024)
In order to promote the nourishment of carp in farming, four foods have been created from traditional raw materials and containing different quantities of locally produced banana flour 3%, 6%, 10%. We tested these foods which contain 36% crude proteins and 8% lipids on carp fry with an initial weight of 9g. After 50 days of experiment, the final weights of the fish fluctuated between 121.53g and 122.45g depending on the treatments used. The food containing 10% banana flour and the control food showed the highest growth and food transformation rates, with specific growth rates (SGR) of 5.18%/d and 5.14% /d as well as a conversion rate of 1.17 and 1.15 while the food with 6% banana flour obtained a SGR of 5.15 and a conversion index (CI) of 1.15 while that the food with 3% obtained a SGR of 5.14 and a CI of 1.16. Thanks to this test, we were able to observe the impact of bananas on the premature development of tilapia. We will continue to study the use of local agri-food by-products and waste in feeding this fish.